Gold as an Inflation Hedge: Long term and short term evidence with allowances for structural breaks - Roddha, Angad C (2013)
This paper investigates if investment in gold really is an effective hedge against inflation in the US for the long run as well as the short run. It studies the annual price of gold over the entire period since it has been freely floated i.e. from 1971 to 2012 along with the annual CPI figures for the same period. Both the gold prices and the price index data were sourced from the World Gold Council. The data was split in to two sub groups; 1971-1981 and 1981-2012.